Optically anisotropic substrates via wrinkle-assisted convective assembly of gold nanorods on macroscopic areas - Tebbe, Moritz; Mayer, Martin; Glatz, Bernhard A.; Hanske, Christoph; Probst, Patrick T.; Mueller, Mareen B.; Karg, Matthias; Chanana, Munish; Koenig, Tobias A. F.; Kuttner, Christian; Fery, Andreas (Faraday Discussions, 2015)
We demonstrate the large-scale organisation of anisotropic nanoparticles into linear assemblies displaying optical anisotropy on macroscopic areas. Monodisperse gold nanorods with a hydrophilic protein shell are arranged by dip-coating on wrinkled surfaces and subsequently transferred to indium tin oxide (ITO) substrates by capillary transfer printing. We elucidate how tuning the wrinkle amplitude enables us to precisely adjust the assembly morphology and fabricate single, double and triple nanorod lines. For the single lines, we quantify the order parameter of the assemblies as well as interparticle distances from scanning electron microscopy (SEM) images. We find an order parameter of 0.97 and a mean interparticle gap size of 7 nm. This combination of close to perfect uni-axial alignment and close-packing gives rise to pronounced macroscopic anisotropic optical properties due to strong plasmonic coupling. We characterise the optical response of the assemblies on ITO-coated glass via UV/vis/NIR spectroscopy and determine an optical order parameter of 0.91. The assemblies are thus plasmonic metamaterials, as their periodicity and building block sizes are well below the optical wavelength. The presented approach does not rely on lithographic patterning and provides access to functional materials, which could have applications in subwavelength waveguiding, photovoltaics, and for large-area metamaterial fabrication.
CRIS-Team Scopus Importer:2023-03-20